Urinary Tract Infection (UTI) caused by Extended-Spectrum Beta-Lactamase (ESBL)-producing Enterobacteriaceae: a case series - Qonita Imma Irfani; Dessy Kurnia Sari; Dewi Purbaningsih; Tri Wibawa; Titik Nuryastuti (Journal of Clinical Microbiology and Infectious Diseases, 2021)
Introduction: A urinary tract infection (UTI) is an infection in any part of the urinary system, occurring in the kidneys, bladder, ureters, and urethra. UTI incidence in Indonesia was high enough. The prevalence of UTI in the community enhances in line with the increase of age. 40-60 years had a prevalence rate of 3.2%, while at the age of  ≥65, a UTI had a prevalence rate of 20%. UTIs are among the most common infections in humans. Enterobacteria that produce extended-spectrum beta-lactamase (ESBL) is one of the most frequent causes. Prevalence of the ESBL bacterial infection is developing due to the widespread prescription of antibiotics around the world. Thus, our articles established several UTI cases of various ages and their antibiotic susceptibility. Case Description: This case report series presents eight cases describing a UTI caused by Enterobacteriaceae producing ESBL in various ages. Data were collected retrospectively from secondary sources of laboratory results. Patient baby-child mostly had a history of sepsis. Other than that patient had hydronephrosis kidney, seizure, fever. On the other hand, the patient's old man and woman had a history of fever, shock spinal and fracture, malignancy. All patients were tested for antibiotic susceptibility and mostly still sensitive with amikacin, meropenem, nitrofurantoin, and fosfomycin. Conclusions: Our case series established that patients with UTI were mainly still sensitive to amikacin, meropenem, nitrofurantoin, and fosfomycin. We should implement and maintain contact precautions throughout the hospital wards to prevent the transmission of ESBL infections.